The Development of Managerial Assumptions about Human Nature in China: A Tale from Quanzhou - Zhang, Yi-Bing (Cultural and religious studies, 2017)
How managers’ knowledge and beliefs of human nature are formed and manifested has not been fully explored in the context of Chinese society going through rapid transition nowadays. And yet this could be the missing link in our discourse on Chinese managers. Based on a qualitative study conducted in Quanzhou, China, this study found certain assumptions of human nature that are deeply embedded in their managers’ intellectual framework, which in turn guide their managerial behaviours in diverse aspects of their work. Unless the managers are prepared to examine their own thoughts, especially those at the sub-conscious level, they would remain prisoners of their own thought, and all the efforts directed at transforming managers would be seriously compromised.